The Effect Of Warm Compresses On Reducing Back Pain Intensity In Last-Trimester Pregnant Women - Susanti, Novita; Priasmoro, Dian Pitaloka (Jurnal Penelitian Keperawatan Kontemporer, 2026)
Background: Pain is a common complaint experienced by pregnant women as a result of physiological and biomechanical changes in the body approaching childbirth. Pain that is not properly managed can affect comfort, sleep quality, and the psychological condition of pregnant women. One non-pharmacological method that is simple, safe, and effective is the application of warm compresses. This study aims to determine the effect of warm compresses on reducing pain intensity in pregnant women. Objective: This study aims to examine whether warm compresses have an effect on pain intensity in pregnant women and can be recommended as a non-pharmacological intervention. Methods: This study employed a pre-experimental design with a one-group pretest–posttest approach. The sample consisted of third-trimester pregnant women experiencing pain who met the inclusion criteria. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after the application of warm compresses. Results: The results showed that most respondents experienced moderate pain before the application of warm compresses. Following the intervention, the majority of respondents reported a decrease in pain intensity, categorized as mild. Statistically, there was a significant difference between pain intensity before and after the application of warm compresses, indicating that warm compresses reduced pain intensity in pregnant women. Conclusion: Based on the study results, it can be concluded that the application of warm compresses reduces pain intensity in pregnant women. Warm compresses are an effective, safe, and easy-to-apply non-pharmacological method to improve the comfort of pregnant women.